Obsessed With Life Reflected in Rupert Sandersâs Snow White and The Huntsman Movie (2012): A Psychoanalytic Perspective - Rosiani, Adili (JoLLIET, 2014)
This study is about how obsessed with life reflected in Rupert Sanderâs Snow White and the Huntsman movie (2012) by using a psychoanalytic approach. The objectives of the study are to analyze the movie based on its structural elements and to analyze the movie based on psychoanalytic approach.The writer uses qualitative method for analyzing the movie. The object of the study is Snow White and the Huntsman movieâs (2012) by Rupert Sander. It will be analyzed through Psychoanalytic Approach. The primary data is taken from the movie itself and the secondary data sources are books or any information that are relevant to the subject matter. The techniques of collecting the data are watching the movie repeatedly, taking notes of important parts both primary and secondary data, arranging the data into several groups based on its theoretical category, selecting particular parts considered important and relevant for analysis, drawing conclusion and formulate its pedagogical suggestion. The technique of data analysis is descriptive analysis.Â Â Â Â Â Â Based on the analysis, the researcher draws the following conclusions. First, based on the structural analysis of each element, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise-en-scene, cinematography, sound, and editing are related to each other. Second, based on psychoanalytic analysis, it shows that Snow White and the Huntsman wants to convey a message that the people maximasize obsession in order to have a good experience of life.